2021
DOI: 10.1080/09553002.2021.1962572
|View full text |Cite
|
Sign up to set email alerts
|

Low dose ionizing radiation and the immune response: what is the role of non-targeted effects?

Abstract: Objectives: This review aims to trace the historical narrative surrounding the low dose effects of radiation on the immune system and how our understanding has changed from the beginning of the 20th century to now. The particular focus is on the non-targeted effects (NTEs) of low dose ionizing radiation (LDIR) which are effects that occur when irradiated cells emit signals that cause effects in the nearby or distant non-irradiated cells known as radiation induced bystander effect (RIBE). Moreover, radiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 183 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…Previous studies demonstrated a well correlated normal liver functional mapping by using sulfur colloid (SC), single-photon emission computed tomography (SPECT), computed tomography (CT) [33] , or deformable image registration (DIR) [34] methods, more treatment-related details in patients with higher normal liver dosage need to be studied using these techniques. In the era of immunotherapy and the abscopal effect, more attentions are necessary to radiation-induced immune response, such as the non-target effect caused by low dose ionizing radiation, which includes damage or response in the nearby or distant tissues [35] , our study might be useful for the future studies in determining whether the dosage is immune-stimulative or immune-suppressive, thus might guide the combination of immunotherapy or other chemotherapy usage given that several clinical trials have already proved some patients with HCC can benefit from the immune checkpoint inhibitors(ICIs) and system therapy [36] , [37] , [38] . In the previous study, a mean hepatic tolerable physical radiation dose of 21 and 6 Gy for the whole liver was appropriate to prevent RILD in patients with Child-Pugh classes A and B, respectively [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated a well correlated normal liver functional mapping by using sulfur colloid (SC), single-photon emission computed tomography (SPECT), computed tomography (CT) [33] , or deformable image registration (DIR) [34] methods, more treatment-related details in patients with higher normal liver dosage need to be studied using these techniques. In the era of immunotherapy and the abscopal effect, more attentions are necessary to radiation-induced immune response, such as the non-target effect caused by low dose ionizing radiation, which includes damage or response in the nearby or distant tissues [35] , our study might be useful for the future studies in determining whether the dosage is immune-stimulative or immune-suppressive, thus might guide the combination of immunotherapy or other chemotherapy usage given that several clinical trials have already proved some patients with HCC can benefit from the immune checkpoint inhibitors(ICIs) and system therapy [36] , [37] , [38] . In the previous study, a mean hepatic tolerable physical radiation dose of 21 and 6 Gy for the whole liver was appropriate to prevent RILD in patients with Child-Pugh classes A and B, respectively [39] .…”
Section: Discussionmentioning
confidence: 99%
“…It does not appear to have been documented as a direct consequence of a non-irradiated organism receiving bystander signals. A review of the literature aimed at answering the question of whether low doses stimulate the immune response also produced many contradictory findings [307]. This again points to the complexity of low-dose and non-targeted responses, where many competing processes are in play.…”
Section: Low-dose Mechanismsmentioning
confidence: 99%
“…In the case of low dose radiation exposures, cancer, cardiovascular disease, foetal abnormality, and chronic fatigue are examples of gross adverse effects [ 89 ]. These are thought to result from genomic instability, mutation in critical genes, microenvironment alterations leading to niche compromise, haematological insufficiency and immune dysfunction [ 7 , 29 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. These in turn are attributed to DNA damage, elevated ROS, mitochondrial insufficiency, membrane channel imbalances and failure of “checks and balances” on the rate of specific enzyme reactions, leading to tipping points where metabolic malfunction occurs.…”
Section: Downstream Events—the Role Of Ribe and Rigimentioning
confidence: 99%
“…These ideas are fiercely unpopular among those who wish to promote a threshold model of radiation protection because any possibility that radiation might cause any adverse low dose effects, means that a precautionary approach is likely to be retained when setting dose limits [ 21 , 22 , 23 , 24 ]. The reality is that low dose hypersensitivity exists [ 25 , 26 , 27 , 28 ] and non-targeted effects (discussed in the next section), can result in both “good” and “bad” effects [ 2 , 29 , 30 , 31 , 32 ]. The debate should not really be centered on whether low doses of radiation are good or bad but should be concerned with how systems deal with low doses of stressors and whether improved modelling or approaches such as adverse outcome pathway (AOP) analysis can improve our ability to understand and thus predict individual responses.…”
Section: Introduction To Low Dose and Non-targeted Radiobiologymentioning
confidence: 99%